"Am I Not a Woman and a Sister:" Activist Performance in Antebellum Black Women's Literary Societies - Herron, Jennifer. (2017)
Abstract: The 1830s saw a proliferation of black women's literary societies across the antebellum North. The rise of these organizations coincided with an uptick in anti-slavery activity, and with the dawning of the early women's rights movement. This thesis explores the work of three such societies and questions how they intervened in the political discourses of their local and national communities. The first chapter explores Philadelphia's Female Literary Association through the records of their performances as published in The Liberator. The second chapter focuses on Boston's Afric-American Female Intelligence Society, interpreting the work of this under-documented organization by locating it within the social, economic, and activist cultures of its time. The third chapter examines New York City's Ladies' Literary Society through a study of their Third Anniversary Celebration. This thesis argues that the societies listed above used various forms of performance to publicly promote racial and gender equality.; Thesis (M.A.)--Tufts University, 2016.; Submitted to the Dept. of Drama.; Advisor: Heather Nathans.; Committee: Noe Montez, and Kendra Field.; Keywords: Theater history, African American studies, and Women's studies.